2022
DOI: 10.1101/2022.08.19.504595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical and Heat Hyperalgesia upon Withdrawal from Chronic Intermittent Ethanol Vapor depends on Sex, Exposure Duration and Blood Alcohol Concentration in Mice

Abstract: Approximately half of patients with alcohol use disorder (AUD) report pain and this can be severe during withdrawal. However, many questions remain regarding the importance of sex, blood alcohol concentration (BAC), time course, and pain modality. To examine the impact of sex and BAC on the time course of the development of mechanical and heat hyperalgesia, we characterized a mouse model of Chronic Alcohol Withdrawal Induced Pain (CAWIP) in the presence or absence the alcohol dehydrogenase inhibitor, pyrazole.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Moreover, Brandner et al (2023) demonstrated a sex difference in hypersensitivity-state during the 4 weeks of CIE model, in which vapour exposure produced heat hyperalgesia only in female and not in male mice (Brandner et al, 2023), and the dependent mice developed a strong hypersensitivity as early as the first hours of abstinence (8-72 h). A limitation of the current work is the lack of a longer timecourse, but future studies will assess additional time points to clarify the trend over time and the resolution of hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Brandner et al (2023) demonstrated a sex difference in hypersensitivity-state during the 4 weeks of CIE model, in which vapour exposure produced heat hyperalgesia only in female and not in male mice (Brandner et al, 2023), and the dependent mice developed a strong hypersensitivity as early as the first hours of abstinence (8-72 h). A limitation of the current work is the lack of a longer timecourse, but future studies will assess additional time points to clarify the trend over time and the resolution of hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The rat models of the chronic ethanol exposure reported mechanical allodynia (Edwards et al, 2012) and hyperalgesia (Avegno et al, 2018;Roltsch Hellard et al, 2017) in the dependent male rats undergoing withdrawal. Recent mouse studies have reported sex-and time course-specific mechanical and heat hyperalgesia during the alcohol withdrawal (Brandner et al, 2023).…”
Section: Introductionmentioning
confidence: 99%